Developing a Mangrove Ecotourism Model through Local Economy: Implications for Ecosystem Sustainability in Urban Coastal Areas - Anggraeny Puspaningtyas; Ghulam Maulana Ilman (Journal Public Policy, 2026)
Mangrove ecotourism development in urban coastal areas faces complex challenges, including pressures from urbanization and the need for sustainable local economic growth. This study aims to develop a Local Economic Development (LED)-based model for Mangrove Ecotourism in Gunung Anyar Tambak, Surabaya, by applying Blakely's four LED dimensions: locality development, business and economic base development, human resource development, and community economic development. A qualitative descriptive approach was used through field observations, in-depth interviews with key stakeholders, and secondary data analysis, including spatial planning and local development policies. The findings indicate that Gunung Anyar Tambak has strong local characteristics as an urban coastal mangrove ecosystem that provides ecological protection while offering economic potential, but remains vulnerable to urbanization, tidal flooding, and coastal erosion. This study reveals that mangrove ecotourism has generated diverse local economic activities, including tourism services, small businesses, and processed mangrove-based products. However, these remain fragmented and poorly institutionalized. Human resource development and community participation have been initiated through conservation and environmental education programs. Still, their sustainability is constrained by limited capacity-building mechanisms and reliance on government support and corporate social responsibility. This study proposes an integrated LED-based ecotourism model that emphasizes ecological spatial planning, inclusive local business policies, sustainable investment in green human capital, and the strengthening of community economic institutions. The proposed model contributes to the literature by offering a policy-oriented framework for sustainable mangrove ecotourism in an urban coastal context.